Childhood Trauma, DNA Methylation of Stress-Related Genes, and Depression: Findings From Two Monozygotic Twin Studies. Issue 7 (September 2018) - Peng, Hao; Zhu, Yun; Strachan, Eric; Fowler, Emily; Bacus, Tamara; Roy-Byrne, Peter; Goldberg, Jack; Vaccarino, Viola; Zhao, Jinying
ABSTRACT: Objective: DNA methylation has been associated with both early life stress and depression. This study examined the combined association of DNA methylation at multiple CpG probes in five stress-related genes with depressive symptoms and tested whether these genes methylation mediated the association between childhood trauma and depression in two monozygotic (MZ) twin studies. Methods: The current analysis comprised 119 MZ twin pairs (84 male pairs [mean = 55 years] and 35 female pairs [mean = 36 years]). Peripheral blood DNA methylation of five stress-related genes ( BDNF, NR3C1, SLC6A4, MAOA, and MAOB ) was quantified by bisulfite pyrosequencing or 450K BeadChip. We applied generalized Poisson linear-mixed models to examine the association between each single CpG methylation and depressive symptoms. The joint associations of multiple CpGs in a single gene or all five stress-related genes as a pathway were tested by weighted truncated product method. Mediation analysis was conducted to test the potential mediating effect of stress gene methylation on the relationship between childhood trauma and depressive symptoms. Results: Multiple CpG probes showed nominal individual associations, but very few survived multiple testing. Gene-based or gene-set approach, however, revealed significant joint associations of DNA methylation in all five stress-related genes with depressive symptoms in both studies. Moreover, two CpG probes in the BDNF and NR3C1 mediated approximately 20% of the association between childhood trauma and depressive symptoms. Conclusions: DNA methylation at multiple CpG sites are jointly associated with depressive symptoms and partly mediates the association between childhood trauma and depression. Our results highlight the importance of testing the combined effects of multiple CpG loci on complex traits and may unravel a molecular mechanism through which adverse early life experiences are biologically embedded. Abstract : Supplemental digital content is available in the text.